Composite negative electrode for low-temperature sodium metal battery and preparation method of composite negative electrode

By preparing NaF powder by freeze-drying in sodium metal batteries and embedded in metal sodium foil by mechanical rolling, the problem of capacity decay and low safety performance of sodium metal batteries in low temperature environments is solved, and efficient preparation technology and good battery performance are achieved.

CN119560499APending Publication Date: 2025-03-04CHONGQING INST OF NEW ENE STOR MATER & EQUIP

Patent Information

Application Number
CN202411801398.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Existing sodium metal batteries have problems of capacity decline and low safety performance in low temperature environments, and the existing technology has complex preparation processes and high risk, so they cannot be produced in large quantities.

Method used

NaF powder was prepared by freeze-drying, and NaF was embedded in metal sodium foil by mechanical rolling to prepare NaF@Na composite negative electrode material.

Benefits of technology

It improves the discharge specific capacity and cycling performance of sodium metal batteries in low temperature environments, simplifies the preparation process, reduces safety risks, and realizes the possibility of mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560499A_ABST
    Figure CN119560499A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium metal batteries, and discloses a composite negative electrode for a low-temperature sodium metal battery, which comprises sodium metal and NaF embedded on the surface or inside the sodium metal, the preparation method comprises the following steps: S1, preparing NaF powder by adopting a freeze-drying method; and S2, rolling the NaF powder prepared in the step S1 into a metal sodium foil by adopting a mechanical rolling mode to prepare the NaF-Na composite negative electrode material. According to the technical scheme, the problems that in the prior art, the preparation process is complex, danger is high, and mass production cannot be achieved can be solved, and meanwhile it is ensured that the composite negative electrode has high specific discharge capacity and excellent cycle performance in the low-temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium metal batteries, and in particular to a composite negative electrode for a low-temperature sodium metal battery and a preparation method thereof. Background Art

[0002] With the rapid development of social economy, electronic products and portable devices are widely integrated into people's lives, which makes the demand for efficient and economical energy storage systems more urgent. At present, traditional lithium-ion batteries occupy an important position in the field of energy storage. However, due to the limited lithium resources and the continuous increase in costs, people are actively looking for alternative energy storage solutions.

[0003] In this context, sodium metal has attracted much attention due to its significant advantages. Sodium metal has a high theoretical specific capacity, which can provide a strong energy storage capacity for batteries; its electrode potential is low, which can provide a relatively stable power output for electronic devices; at the same time, it is low in cost, which has obvious advantages over lithium resources. Therefore, sodium metal is considered to be an ideal substitute for lithium metal anode in the future.

[0004] However, sodium metal still faces many challenges when used as anode in batteries. On the one hand, the uncontrollable growth of sodium dendrites, volume expansion, and interface instability lead to defects in sodium metal batteries such as low Coulombic efficiency, poor cycle performance, and low safety performance. On the other hand, in low temperature (<-20°C) environments, the slow ion transfer kinetics at the sodium metal interface can cause severe capacity decay and even lead to battery failure.

[0005] The existing technical solution with patent number CN109802129B discloses a metal sodium battery negative electrode material and its preparation method and application. Although this solution solves the problem of sodium dendrite growth by introducing nanometal nucleation sites, it has the defects of complex preparation process, high risk and inability to mass produce. In addition, the electrochemical performance it exhibits is only tested at room temperature, and the battery performance in low temperature environment (<-20℃) is still unclear. Summary of the invention

[0006] The present invention aims to provide a composite negative electrode for a low-temperature sodium metal battery and a preparation method thereof, so as to solve the problems existing in the prior art of complex preparation process, high risk and inability to produce in large quantities, while ensuring that the composite negative electrode has a high discharge specific capacity and excellent cycle performance in a low-temperature environment.

[0007] To achieve the above object, the present invention adopts the following technical solution: a composite negative electrode for a low-temperature sodium metal battery, comprising sodium metal and NaF embedded on the surface or inside of the metallic sodium.

[0008] Preferably, the mass percentage of metallic sodium and NaF is (4.5-5.5):1.

[0009] The present invention also provides another technical solution, a method for preparing a composite negative electrode for a low-temperature sodium metal battery, comprising the following steps:

[0010] S1: NaF powder was prepared by freeze drying;

[0011] S2: The NaF powder prepared in S1 was rolled into a metallic sodium foil by mechanical rolling to obtain a NaF@Na composite negative electrode material.

[0012] Preferably, in S1, the NaF powder is prepared by freeze drying, comprising the following steps:

[0013] S1.1: Weigh a certain amount of NaOH and dissolve it in deionized water;

[0014] S1.2: Add a certain amount of HF to the solution obtained in S1.1, stir for 15-20 minutes, and then freeze-dry to obtain NaF powder.

[0015] Preferably, the molar ratio of NaOH to HF is 1:(1-1.03).

[0016] Preferably, the freeze-drying process is: first, freeze the solution in S1.2 at -40°C for 24-28 hours, and then dry it in a freeze dryer for 48-50 hours, wherein the vacuum degree of the freeze dryer is less than 20 Pa.

[0017] Preferably, the mechanical rolling process in S2 is: in a glove box free of water and oxygen, NaF is evenly dispersed on a metallic sodium foil, and the NaF@Na composite negative electrode material is prepared by manual rolling back and forth for 30-40 times.

[0018] Preferably, in S2, the thickness of the prepared NaF@Na composite negative electrode material is 200-400 μm.

[0019] Preferably, in S1.2, the concentration of HF is 20-25 moL / L.

[0020] Compared with the prior art, the beneficial effects of this solution are:

[0021] The present technical solution firstly adopts a freeze-drying method to prepare a crystalline sodium fluoride (NaF) material, and then rolls it into a metallic sodium foil by mechanical rolling, thereby preparing a NaF@Na composite negative electrode material.

[0022] From the perspective of preparation technology, freeze-drying can accurately control the formation process of NaF, effectively ensuring its purity and stability of crystal structure. In the entire preparation process, there are no complicated chemical reaction steps, nor expensive equipment investment, and the operation is extremely simple. The mechanical rolling method is used to embed NaF into metallic sodium foil, and the operation process is also relatively simple.

[0023] From the perspective of safety, compared with traditional preparation methods, this solution does not involve high temperature, high pressure, or flammable and explosive chemicals during the preparation process, which greatly reduces safety risks. Whether in laboratory environments or industrial production, it can provide operators with safer and more reliable working conditions, effectively reducing the possibility of safety accidents caused by improper operation.

[0024] In terms of achieving mass production, the preparation scheme shows high repeatability and stability. Both freeze-drying equipment and mechanical roller pressing equipment can achieve continuous production, and the equipment operating costs are relatively low. Through reasonable process design and equipment selection, the production scale can be easily expanded to meet the large market demand for products. At the same time, due to the simple preparation process and low risk, the consistency of product quality can be better guaranteed during large-scale production, thereby improving production efficiency and reducing production costs, laying a solid foundation for the widespread application of composite negative electrodes for sodium metal batteries.

[0025] The introduction of NaF greatly improved the electrolyte / Na negative electrode interface stability and effectively inhibited the growth of sodium dendrites, thereby extending the cycle life of sodium metal batteries.

[0026] The introduction of NaF effectively improves the ion transfer kinetics of sodium ions at the interface of the sodium metal anode. Even at low temperature (-40°C), the full battery (NaF@Na||NVP) assembled using this composite anode has a high discharge specific capacity and cycle performance.

[0027] The NaF powder prepared by the freeze-drying method adopted in this technical solution presents a flocculent morphology, and the synthesized flocculent NaF powder is close to the nanometer level, and has the characteristics of being soft and easy to deform. In the process of rolling it into the metallic sodium foil by mechanical rolling, even if NaF does not react with Na metal, it can promote the uniform distribution of NaF in Na metal, and ensure that the surface of the NaF@Na negative electrode is flat and there will be no bulges. However, commercially available NaF usually appears in granular form. Even if this granular NaF is rolled with sodium metal and evenly distributed, NaF still exists in the sodium metal in the form of particles, which will cause NaF particles to bulge on the surface of the NaF@Na composite negative electrode, and this uneven surface will aggravate the growth of sodium dendrites, thereby producing the opposite effect.

[0028] The technical solution uses NaOH and HF in a molar ratio of 1: (1-1.03) to prepare NaF powder, so that HF ​​is slightly excessive, so that NaOH reacts completely, and the prepared NaF has high purity and does not contain NaHF2 impurities. If NaOH is replaced with sodium carbonate, the NaF synthesized from sodium carbonate and HF will contain NaHF2 impurities. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 (a) is an electronic image of NaF in Example 1 of the present invention and purchased NaF;

[0030] Figure 1 (b) is a SEM image of NaF in Example 1 of the present invention;

[0031] Figure 1 (c) is the SEM image of purchased NaF;

[0032] Figure 2 (a) is the XRD pattern of NaF in Example 1 of the present invention;

[0033] Figure 2 (b) is the EIS graph of the symmetric cell of 20% NaF@Na, 10% NaF@Na, 30% NaF@Na and metallic sodium prepared in Example 1 of the present invention and Comparative Examples 1-3;

[0034] Figure 3 (a) is the current density of 0.1 mA / cm 2 , the deposition amount is 0.1mAh / cm 2 Under the conditions of , a symmetrical battery assembled with 20% NaF@Na prepared in Example 1 and the metallic sodium negative electrode material of Comparative Example 3 was tested for cycle performance with a constant deposition amount;

[0035] Figure 3 (b) is the current density of 0.5 mA / cm 2 , the deposition amount is 0.5mAh / cm 2 Under the conditions of , the symmetrical battery assembled with 20% NaF@Na prepared in Example 1 and P-NaF@Na prepared in Comparative Example 4 was tested for the cycling performance with a constant deposition amount;

[0036] Figure 4 (a) is a SEM image of the metallic sodium negative electrode before cycling in Comparative Example 3 of the present invention;

[0037] Figure 4 (b) is a SEM image of the metal sodium negative electrode in Comparative Example 3 of the present invention after 10 cycles;

[0038] Figure 4(c) is a SEM image of the 20% NaF@Na negative electrode prepared in Example 1 of the present invention after 10 cycles;

[0039] Figure 5 (a) Cyclic performance of the NVP||NaF@Na full cell assembled with 20% NaF@Na prepared in Example 1 of the present invention at -20°C and a current density of 1C;

[0040] Figure 5 (b) Cyclic performance of the NVP||NaF@Na full battery assembled with 20% NaF@Na prepared in Example 1 of the present invention at -40°C and a current density of 0.1C;

[0041] Figure 5 (c) Cycling performance of the NVP||NaF@Na full battery assembled with 20% NaF@Na prepared in Example 1 of the present invention at -40°C and a current density of 0.2C;

[0042] Figure 6 The charge and discharge curves of the NVP||Na full battery assembled with metallic sodium in Comparative Example 3 at -40°C and a current density of 0.2C are shown in the figure. DETAILED DESCRIPTION

[0043] The following is further described in detail through specific implementation methods:

[0044] Example 1

[0045] A composite negative electrode for a low-temperature sodium metal battery comprises sodium metal and NaF embedded on the surface or inside of the sodium metal, wherein the mass percentage of the sodium metal and the NaF is (4.5-5.5):1. In this embodiment, the mass percentage of the sodium metal and the NaF is 10:2.

[0046] A method for preparing a composite negative electrode for a low-temperature sodium metal battery comprises the following steps:

[0047] S1: NaF powder was prepared by freeze drying;

[0048] S1.1: Weigh 503.56 mg of NaOH and dissolve it in 200 mL of deionized water. Stir and mix well at room temperature.

[0049] S1.2: Add 600 μL of HF to the solution obtained in S1.1, the molar ratio of NaOH to HF is 1:(1-1.03), the concentration of HF is 20-25 mol / L, stir for 15-20 min, and then freeze-dry. The freeze-drying process is as follows: first freeze the solution at -40°C for 24-28 h, and then dry it in a freeze dryer for 48-50 h, and the vacuum degree of the freeze dryer is less than 20 pa; in this embodiment, stir for 15 min, and then freeze-dry. Freeze at -40°C for 24 h, and then dry it in a freeze dryer for 48 h, and the vacuum degree of the freeze dryer is 18 pa; the concentration of HF is 22.8 mol / L;

[0050] S2: The NaF powder prepared in S1 is rolled into a metallic sodium foil by mechanical rolling, and the mass percentage of metallic sodium and NaF is 10:2, to obtain a NaF@Na composite negative electrode material, recorded as 20% NaF@Na; wherein the process of mechanical rolling is: in a glove box free of water and oxygen, NaF is evenly dispersed on the metallic sodium foil, and the NaF@Na composite negative electrode material is obtained by manual rolling back and forth 30-40 times; the thickness of the obtained NaF@Na composite negative electrode material is: 200-400μm; in this embodiment, the NaF@Na composite negative electrode material is obtained by manual rolling back and forth 30 times, and the thickness of the obtained NaF@Na composite negative electrode material is: 300μm.

[0051] Comparative Example 1

[0052] Different from Example 1, in a composite negative electrode for a low-temperature sodium metal battery, the mass percentage of metallic sodium and NaF is 10:1; in a method for preparing a composite negative electrode for a low-temperature sodium metal battery, in S2, the NaF powder prepared in S1 is rolled into a metallic sodium foil by mechanical rolling, and the mass percentage of metallic sodium and NaF is 10:1, to obtain a NaF@Na composite negative electrode material, recorded as 10% NaF@Na.

[0053] Comparative Example 2

[0054] Different from Example 1, in a composite negative electrode for a low-temperature sodium metal battery, the mass percentage of metallic sodium and NaF is 10:3; in a method for preparing a composite negative electrode for a low-temperature sodium metal battery, in S2, the NaF powder prepared in S1 is rolled into a metallic sodium foil by mechanical rolling, and the mass percentage of metallic sodium and NaF is 10:3, to obtain a NaF@Na composite negative electrode material, recorded as 30% NaF@Na.

[0055] Comparative Example 3

[0056] The difference from Example 1 is that metallic sodium is used as the negative electrode of the sodium metal battery.

[0057] Comparative Example 4

[0058] Different from Example 1, different from Example 1, a method for preparing a composite negative electrode for a low-temperature sodium metal battery, in S2, commercially available NaF powder is rolled into a metallic sodium foil by mechanical rolling, and the mass percentage of metallic sodium and NaF is 5:1, to obtain a P-NaF@Na composite negative electrode material, recorded as P-NaF@Na.

[0059] The various properties of the sodium metal battery negative electrode materials prepared in Example 1 and Comparative Examples 1-4 were tested.

[0060] (1) The commercially available NaF powder and the NaF powder prepared in Example 1 were photographed and observed using a scanning electron microscope. Figure 1 It can be seen that the commercially available NaF powder is granular, with a particle size of nearly 40um, and the NaF powder prepared by the preparation method in Example 1 is flocculent, and the synthesized flocculent NaF powder is close to the nanometer level, with characteristics such as softness and easy deformation. In the process of rolling it into the metal sodium foil by mechanical rolling, even if NaF does not react with Na metal, it can promote NaF to be evenly distributed in Na metal, and ensure that the surface of the NaF@Na negative electrode is flat and there will be no bulges. However, even if the commercially available NaF particles are rolled with sodium metal and evenly distributed, NaF still exists in the sodium metal in the form of particles, which will cause NaF particles to bulge on the surface of the NaF@Na composite negative electrode, and this uneven surface will aggravate the growth of sodium dendrites, thereby producing the opposite effect.

[0061] (2) The NaF material obtained in Example 1 was subjected to XRD test. Figure 1 (a) It can be seen that NaF material was successfully prepared by freeze-drying method.

[0062] (3) Using EIS (electrochemical impedance spectroscopy) to test the effect of different proportions of NaF on the electrochemical performance of the battery

[0063] The 20% NaF@Na prepared in Example 1, the 10% NaF@Na prepared in Comparative Example 1, the 30% NaF@Na prepared in Comparative Example 2, and the metallic sodium negative electrode materials of Comparative Example 3 are respectively assembled into symmetrical batteries. Now, taking Example 1 as an example for explanation, the specific operation is as follows: 20% NaF@Na is used as the positive and negative electrode materials of the battery respectively, a glass fiber diaphragm (GF) is selected as the diaphragm material, and 1moL / L NaClO4 in PC=100vol%with 5%FEC is used as the electrolyte to assemble button batteries. The symmetrical battery assembly process of Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4 is the same as that of Example 1, and will not be repeated here. EIS (electrochemical impedance spectroscopy) was used to test the effects of different proportions of NaF on the electrochemical performance of the battery. Figure 2 (b) It can be seen that the 20% NaF@Na negative electrode exhibits the lowest charge transfer impedance, indicating that the reaction kinetics of the 20% NaF@Na prepared in Example 1 is the best.

[0064] (3) Exploring the ability of composite negative electrodes to stabilize sodium plating and stripping

[0065] The 20% NaF@Na prepared in Example 1, the metallic sodium negative electrode material of Comparative Example 3, and the P-NaF@Na prepared in Comparative Example 4 were assembled into symmetrical batteries and charged at a current density of 0.1 mA / cm 2 And the deposition amount is 0.1mAh / cm 2 The cycle performance test of constant deposition amount was carried out under the condition of current density of 0.5mA / cm 2 and a deposition capacity of 0.5 mAh / cm 2 The cycle performance test of constant deposition amount was also carried out under the condition of Figure 3 (a) and 3(b) show that the 20% NaF@Na electrode can be stably cycled for 3800 h, indicating that the Na negative electrode has excellent reversibility under the protection of NaF and effectively inhibits the growth of sodium dendrites. Even if the current density and deposition capacity are increased to 0.5 mA / cm 2 and 0.5mAh / cm 2 The symmetrical battery assembled with 20% NaF@Na electrode can still stably cycle for nearly 1400h, and the overpotential during the cycle is basically maintained at around 100mV, while the Na||Na symmetrical battery without NaF has short circuited in less than 200h, which indicates that the presence of NaF regulates the Na + The electroplating behavior inhibits the growth of sodium dendrites and improves the cycle life of the battery; the symmetrical battery assembled with P-NaF@Na electrode can only cycle for 220h, and the polarization voltage is also slightly larger than that of the symmetrical battery assembled with 20% NaF@Na electrode.

[0066] (4) Further verification of the role of NaF in regulating sodium ion deposition and stripping

[0067] The 20% NaF@Na prepared in Example 1 and the metallic sodium negative electrode material of Comparative Example 3 were assembled into symmetrical cells respectively. 2 And the deposition amount is 0.5mAh / cm 2 Under the condition of constant deposition amount, the cycle performance test was carried out. After 10 cycles, SEM images of different electrode surfaces were taken using a scanning electron microscope. Figure 4 (a), 4(b) and 4(c), it can be seen that in the absence of NaF, the electrode showed uneven deposition and formed uneven bulk sodium deposition. On the contrary, after 10 cycles of the assembled 20%NaF@Na||20%NaF@Na symmetric battery, the surface of the 20%NaF@Na electrode was dense and flat, which again shows that the presence of NaF can promote the uniform deposition of sodium ions and inhibit the formation of sodium dendrites.

[0068] (6) Further confirm the feasibility of 20% NaF@Na electrode in practical applications

[0069] The 20% NaF@Na prepared in Example 1 and the metal sodium negative electrode material of Comparative Example 3 are respectively assembled into full batteries. Example 1 is now used as an example for description. The specific operation is as follows: 20% NaF@Na is used as the negative electrode active material of the battery, sodium vanadium phosphate (NVP) is used as the positive electrode active material of the battery, a glass fiber separator (GF) is selected as the separator material, and 1 mol / L NaClO4 in PC = 100 vol% with 5% FEC is used as the electrolyte to assemble the button battery. The full battery assembly process of Comparative Example 3 is the same as that of Example 1, and will not be repeated here.

[0070] Under low temperature conditions, the electrochemical performance of full batteries assembled with 20% NaF@Na prepared in Example 1 and the metallic sodium negative electrode material of Comparative Example 3 were tested respectively. Figure 5 (a) shows the long cycle performance of NVP||20%NaF@Na full battery at -20℃ and current density of 1C. The first cycle discharge capacity can reach 75.9mAh / g. After 400 cycles, the capacity has almost no decay, and the average coulombic efficiency is close to 100%. In order to further verify the advantages of 20%NaF@Na negative electrode at low temperature, we lowered the temperature to -40℃. Figure 5As shown in (b), the first cycle discharge capacity of the NVP||20%NaF@Na full battery at 0.1C can be maintained at 71.9mAh / g. After 25 cycles, the temperature is raised to 25°C, and the discharge capacity of the NVP||20%NaF@Na full battery is still close to that of the battery cycled normally at room temperature. After 10 cycles, the test temperature is lowered to -40°C again, and the battery can still cycle normally with almost no capacity decay. Figure 5 As shown in (c), even if the current density is increased to 0.2C, the battery can still work normally. Figure 6 As shown in Figure 2, the assembled NVP||Na battery short-circuited in the first cycle at -40 degrees. This shows that the introduction of NaF regulates the Na + The electroplating behavior of NaF was improved and the growth of sodium dendrites was effectively suppressed. At the same time, NaF has high ionic conductivity and high charge transfer kinetics at the negative electrode interface even at low temperatures, ensuring the normal operation of the battery.

[0071] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A composite negative electrode for a low-temperature sodium metal battery, characterized in that: It includes sodium metal and NaF embedded on the surface or inside of metallic sodium.

2. The composite negative electrode for a low-temperature sodium metal battery according to claim 1, characterized in that: The mass percentage of metallic sodium and NaF is (4.5-5.5):

1.

3. A method for preparing a composite negative electrode for a low-temperature sodium metal battery, characterized in that: The following steps are involved: S1: NaF powder was prepared by freeze drying; S2: The NaF powder prepared in S1 was rolled into a metallic sodium foil by mechanical rolling to obtain a NaF@Na composite negative electrode material.

4. The method for preparing a composite negative electrode for a low-temperature sodium metal battery according to claim 3, characterized in that: In S1, NaF powder is prepared by freeze drying, comprising the following steps: S1.1: Weigh a certain amount of NaOH and dissolve it in deionized water; S1.2: Add a certain amount of HF to the solution obtained in S1.1, stir for 15-20 minutes, and then freeze-dry to obtain NaF powder.

5. The method for preparing a composite negative electrode for a low-temperature sodium metal battery according to claim 4, characterized in that: The molar ratio of NaOH to HF is 1:(1-1.03).

6. The method for preparing a composite negative electrode for a low-temperature sodium metal battery according to claim 5, characterized in that: The freeze-drying process is as follows: firstly, the solution in S1.2 is frozen at -40°C for 24-28 hours, and then dried in a freeze dryer for 48-50 hours, and the vacuum degree of the freeze dryer is less than 20 Pa.

7. The method for preparing a composite negative electrode for a low-temperature sodium metal battery according to claim 6, characterized in that: The mechanical rolling process in S2 is as follows: in a glove box free of water and oxygen, NaF is evenly dispersed on a metallic sodium foil, and the NaF@Na composite negative electrode material is obtained by manual rolling back and forth for 30-40 times.

8. The method for preparing a composite negative electrode for a low-temperature sodium metal battery according to claim 7, characterized in that: In S2, the thickness of the prepared NaF@Na composite negative electrode material is 200-400 μm.

9. The method for preparing a composite negative electrode for a low-temperature sodium metal battery according to claim 8, characterized in that: In S1.2, the concentration of HF is 20-25 moL / L.

Citation Information

Patent Citations

  • A sodium metal battery anode material, its preparation method and application

    CN109802129B

  • Preparation method of lithium battery negative electrode material and lithium battery

    CN117613220A

  • Negative electrode material and preparation method and application thereof

    CN118412460A

  • Composite sodium metal negative plate and preparation method and application thereof

    CN119008848A

  • Sodium metal negative electrode surface pretreatment liquid, pretreatment method and application

    CN119029163A

Cited By

  • NaF-doped hard carbon negative electrode composite material as well as preparation method and application thereof

    CN121460545A